Globalization, democracy, and the news media in Nigeria: challenges and prospects - Adie Edward Ugbada (Center for Humanities and Innovation Studies, 2019)
Democracy as a concept of government became universal after the fall of the Berlin wall in 1989, the disbanding of the USSR in 1991, the crumple of communism and the end of the Cold War. Ever since then, this global phenomenon called democracy became the central and most preferred system of government worldwide. It has also been embraced in its entirety though in some cases modified based on the dominant/peculiar cultural and political structure of the people till this present day; except of course for a very few and negligible number of countries that have fervidly refused to embrace it as the best means of leading a people. This pervasive acceptance is predicated on two key elements- which are; globalization and the media. Though the concept of globalization is shrouded in strong arguments between a school of thought known as the skeptics and the other school of the argument known as the globalizers, McLuhan’s Global Village postulation unraveled this controversy by a simple analogy which links the media as the vehicle with which the concept was made popular and acceptable to the clinch of a large followership. In a symbiotic reward, the media was able to carry out its function of news dissemination in democracy, due to higher information technology occasioned by the consequences of globalization. Despite this advantage, the Nigeria democratic experience is one that has not been able to draw from the advantages herein. The country’s democracy is been overwhelmed by different challenges that has affected its emergence since the country attained independence in 1960. However, happening in the 2015 general elections portend a ray of hope for the growth of democracy in the country after which it can then shift its efforts to the consolidation of its democracy.